Prevalence, Clinical Profile and Seasonal Variation of Otomycosis in Pakistan - Ahmed Khan, Muhammad (International Journal of Pathology, 2020)
Objective; To assess prevalence, clinical profile and seasonal variation of otomycosis in Pakistan.Study design, place& duration;Observational study. It was carried outfrom January 2019 to December 2019 at CMH Mardan, Rawalpindi, Lahore, Karachi and Quetta.Material &Methods:The cases with symptoms including itching, pain, decreased hearing, ear blockage, tinnitus and otoscopic findings showing hyphae, spores or curdlike white, grey or black debris/discharge in external auditory meatus of the patient confirmed with fungal culture or presence of fungal elements in 10% potassium hydroxide (KOH) – methylene blue preparation were included. In case of children below 5 years, symptoms including irritability, restlessness, reaching for ear or touching ear repeatedly, less response to audible sounds, unable to turn head to the sound stimulus in previously normal hearing child with otoscopic findings of hyphae, spores or curd-like whitish, greyish or black debris or discharge in ears were assessed. Informed consent was taken from patients. Permission was taken from ethical review board for subject research. All the data including age, gender, symptoms, number of diagnosed cases of otomycosis, month wise and city wise, were recorded. The data was analyzed by SPSS 21 (statistical package for social science). Chi square was used to compare qualitative variables white independent T test was used to assess quantitative variables. P value less than 0.05 was considered as significant.Results; Total 22350 cases of otomycosis were diagnosed in 2019. The age range was from 2 years to 85 years with mean age 35.3 + 7.51 years. There were 9875 (44.2%) males and 12475 (55.8%) females.We calculated prevalence of otomycosis by dividing total number of reported cases in population dependent on these hospitals. The estimated population dependent on these hospitals is 20 lacs (individuals residing in cantonments plus security forces personnel). Prevalence came out to be 1.1%.Most of otomycosis cases were reported from Rawalpindi i.e 10597(47.4%), followed by Lahore 6161 (27.6%) cases, Karachi 3464(15.5%) cases, Mardan 1067(4.8%) cases and Quetta 1061(4.7%) cases. Majority of cases were seen in month of September i.e 3749(16.8%) cases, followed by 3447 cases (15.4%) in August and 2997 (13.4%) cases in October.Conclusion; Otomycosis is a common ear disease which affects all ages and both genders. Otomycosis is prevalent through out the country and through out the yaer but majority of cases occur during hot and humid weather of summers and in rainy season.